Konstruktivisme dalam Revolusi Pendidikan Dasar Era Digital: Refleksi Filosofis Pemikiran Pendidikan Islam dan Implikasi Praktis - nurjannah, Siti; Ahmad Arifi (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Basic education is an important foundation in shaping the character and competencies of the younger generation, especially in the digital era characterized by the integration of technology in the learning process. This article aims to explore the application of the constructivist paradigm in basic education in the digital era, focusing on the relevance of pedagogical values that must be maintained. Through a descriptive-analytical qualitative approach, this study links the thoughts of Islamic education figures, such as Al-Ghazali and Ibn Khaldun, with the modern constructivist theories proposed by Marc Prensky and Jean Baudrillard. The research findings indicate that the constructivist paradigm, which emphasizes the active role of students in building knowledge through experience and interaction, is highly relevant in the context of 21st-century education. Technology, when well integrated, can enrich the learning experience and encourage collaboration and independent exploration. However, challenges such as the digital divide and teachers' skills need to be addressed through educational policies that support equitable access and professional training. The conclusion of this study emphasizes that by integrating constructivist values, basic education can become more adaptive and contextual, preparing students to face challenges in an increasingly complex world. This research makes a significant contribution to the education literature by bridging the gap between theory and practice, as well as offering guidance for education practitioners and policymakers.